Applications of holography and optical data processing : proceedings of the international conference, Jerusalem, August 23-26, 1976 - Marom, E.; Friesem, A. A.; Wiener-Avnear, E. (Pergamon Press, 1977)
Applications of Holography and Optical Data Processing contains the proceedings of the International Conference on Applications of Holography and Optical Data Processing, held in Jerusalem in August 1976. The conference is attended by eminent scientists in the field of optics, characterized by high-level scientific presentations and discussions. The collection is a representation of research on the cutting edge of applied and theoretical optics. The four-day meeting covers topics on holographic applications in medicine, interferometry, display, storage, and retrieval, as well as image processi.